Magnetic resonance semiotics of breast fibroadenomas - S. V. Serebryakova; G. E. Trufanov; V. A. Fokin; E. A. Yukhno (ABV-press, 2014)
Various benign breast abnormalities are diagnosed in 60% of women in Russia today. This is associated with failure of preoperative recognition of the histological class of an identified nodular mass - its detection is an indication for surgical treatment. By using 67 histologically verified breast fibroadenomas (FA) as an example, the authors describe their magnetic resonance semiotics and present the differential diagnostic criteria used during dynamic contrast-enhanced magnetic resonance mammography. FAs are characterized by well-defined uniform outlines, homogeneous internal structure, centrifugal and homogeneous accumulation of contrast media through- out the study, without deforming the breast vasculature around. One of the criteria that permit differential diagnosis of FA with malignan- cies is their estimated vascularization.